MODEL KOMUNIKASI DAN PEMBENTUKAN KONSEP DIRI: Studi Deskriptif Kualitatif mengenai Model Komunikasi Pembimbing dalam Proses Pembentukan Konsep Diri pada Klien di Balai Rehabilitasi Sosial â€œKARTINIâ€ Tawangmangu - Jati, Tawangsari Anindya; Hastasari, Chatia; Y, Firdastin Ruthnia (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2013)
The phenomenon of children on the street is increasingly widespread. This due to the fact that existence is very easy to find particulary in the city center or street even almost all them are disturbing the society, the naughty child and the children on the street tend to live freely with singing on the street and so on. Therefore it needs to establish a positive self concept for naughty child and children on the street. The objective of the research is to determine the comunication model and to classify effective communication model used by conselors in the process of self concept establishment in the client. This research belongs to qualitative descriptive study, data collection techniques used observation and interview. The results of this research is the process of establishing a positive self-concept on the client in social rehabilitation centers â€œKARTINIâ€ Tawangmangu through three stages of social rehabilitation services consists of some guidance such as the guidance of physical, mental, social skill and character. The guidance uses two communication models. The first communication model effective to estabilish a positive self concept in client with the problems such as dropping out of school, hanging out and so on. Mean while the second communication model effective to client which specific problems such as broken home, drunk, sing on the street and so on.